2017
DOI: 10.1111/maps.12875
|View full text |Cite
|
Sign up to set email alerts
|

Petrography, classification, oxygen isotopes, noble gases, and cosmogenic records of Kamargaon (L6) meteorite: The latest fall in India

Abstract: A single piece of meteorite fell on Kamargaon village in the state of Assam in India on November 13, 2015. Based on mineralogical, chemical, and oxygen isotope data, Kamargaon is classified as an L‐chondrite. Homogeneous olivine (Fa: 25 ± 0.7) and low‐Ca pyroxene (Fs: 21 ± 0.4) compositions with percent mean deviation of <2, further suggest that Kamargaon is a coarsely equilibrated, petrologic type 6 chondrite. Kamargaon is thermally metamorphosed with an estimated peak metamorphic temperature of ~800 °C as de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 31 publications
(48 reference statements)
2
13
2
Order By: Relevance
“…The overall spectroscopic analysis of Kamargaon is consistent with the geochemical compositional analysis. While this manuscript was under review, a report on the fall of the Kamargaon meteorite has been reported by Ray et al (2017). Our present study confirms the classification of the meteorite as L6 chondrite.…”
Section: Resultssupporting
confidence: 86%
“…The overall spectroscopic analysis of Kamargaon is consistent with the geochemical compositional analysis. While this manuscript was under review, a report on the fall of the Kamargaon meteorite has been reported by Ray et al (2017). Our present study confirms the classification of the meteorite as L6 chondrite.…”
Section: Resultssupporting
confidence: 86%
“…The presence of plagioclase indicates to weak nature shock 28 in Kamargaon, which have been already reported. 2 The antisymmetric Si-O stretching vibrations and antisymmetric O-Si(Al)-O deformations exhibits in the mid infrared spectra of Kamargaon correspondingly between 800 to 1150cm −1 and 400cm −1 to 500cm −1 . These band profiles are generally depends on the crystalline structure of the silicates and can therefore be used to identify the mineral phases.…”
Section: Resultsmentioning
confidence: 98%
“…The Kamargaon chondrite ( Figure 1) is a single fall (Kamargaon: 26°39ˊ01 ̋ N and 93° 46ˊ 02 ̋ E), on 13th November, 2015; its total known weight 12.095kg. [1][2][3] Earlier studies focused on the compositional analyses of the meteorite and assigned Kamargaon as an L6 ordinary chondrite. [1][2][3] A cosmic ray exposure age of Kamargaon is 7 Ma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations